2008
DOI: 10.1038/onc.2008.179
|View full text |Cite
|
Sign up to set email alerts
|

DAPK2 is a novel E2F1/KLF6 target gene involved in their proapoptotic function

Abstract: Death-associated protein kinase 2 (DAPK2) belongs to a family of proapoptotic Ca 2 þ /calmodulin-regulated serine/ threonine kinases. We recently identified DAPK2 as an enhancing factor during granulocytic differentiation. To identify transcriptional DAPK2 regulators, we cloned 2.7 kb of the 5 0 -flanking region of the DAPK2 gene. We found that E2F1 and Kru¨ppel-like factor 6 (KLF6) strongly activate the DAPK2 promoter. We mapped the E2F1 and KLF6 responsive elements to a GC-rich region 5 0 of exon 1 containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…KLF6 upregulation abolished E2F1 expression, whereas KLF6 downregulation significantly increased E2F1 expression. The previous document demonstrated that E2F1 and KLF6 cooperated in activating the DAPK2 promoter (39). In our study, promoter luciferase reporter and ChIP assays illustrated that KLF6 directly binds to the human E2F1 gene promoter and inactivates it.…”
Section: Discussionmentioning
confidence: 63%
“…KLF6 upregulation abolished E2F1 expression, whereas KLF6 downregulation significantly increased E2F1 expression. The previous document demonstrated that E2F1 and KLF6 cooperated in activating the DAPK2 promoter (39). In our study, promoter luciferase reporter and ChIP assays illustrated that KLF6 directly binds to the human E2F1 gene promoter and inactivates it.…”
Section: Discussionmentioning
confidence: 63%
“…Hence, early reports -in accordance with the published DAPK1 phenotype -suggested an involvement of DAPK2 in apoptosis. Consistently, silencing of DAPK2 in cells exposed to intrinsic or extrinsic death triggers resulted in reduced apoptosis (Britschgi et al, 2008(Britschgi et al, , 2010.…”
Section: The Ambiguous Role Of Dapk2 In the Regulation Of Apoptosismentioning
confidence: 78%
“…Hence, low levels of DAPK2 in myeloid precursor cells could be increased by demethylating agents (Rizzi et al, 2007), and downregulation of DAPK2 expression in Hodgkin lymphoma was associated with DAPK2 promoter hypermethylation (Tur et al, 2009). The transcription factor SP1 was shown to be indispensable for basic DAPK2 promoter activity, with E2F1 and KLF6 transcription factors necessary for further DAPK2 regulation (Britschgi et al, 2008). Several other transcription factors have been implicated in the regulation of DAPK2 transcription.…”
Section: Regulation Of Dapk2 Activitymentioning
confidence: 99%
“…Gene Expression Assays for GABARAPL1, GATE-16, MAP1LC3B and CSF3R used in a 96 well format on the ABI 7500 Sequence detection system were Hs00744468_s1, Hs00371854_m1, Hs00797944_s1 and Hs00167918_m1, respectively (Applied Biosystems, Rotkreuz, Switzerland). HMBS primer and probes have been described previously [28]. …”
Section: Methodsmentioning
confidence: 99%